WZB117 enhanced the anti-tumor effect of apatinib against melanoma via blocking STAT3/PKM2 axis - Zhang, Ren-Shu; Li, Zhi-Ke; Liu, Jie; Deng, Yao-Tiao; Jiang, Yu (Frontiers in Pharmacology, 2022)
Background: Melanoma is the most lethal skin malignant tumor with a short survival once stepping into the metastatic status and poses a therapeutic challenge. Apatinib (a tyrosine kinase inhibitor) is a promising antiangiogenic agent for the treatment of metastatic melanoma. However, antiangiogenic monotherapy is prone to acquired drug resistance and has a limited therapeutic effect. The persistence dependence of glycolytic metabolism in antiangiogenic therapy-resistant cells provides evidence that glycolysis inhibitors may enhance the effect of antiangiogenic therapy. So, this study aimed to investigate whether WZB117 (a specific GLUT1 inhibitor) could enhance the anti-tumor effect of apatinib against melanoma and its potential mechanisms. Methods: We investigated the anti-tumor effects of apatinib alone or in combination with WZB117 on human melanoma cell lines (A375 and SK-MEL-28). The MTT assay determined cell viability and the half-maximal inhibitory concentration (IC50). Multiple drug effect/combination indexes (CI) analysis was conducted to assess interactions between apatinib and WZB117. Signal transducer and activator of transcription 3 (STAT3) pathway measured by western blotting and immunofluorescence staining. RNA expression analyses were performed using the reverse transcription-quantitative PCR method. Results: Apatinib and WZB117 showed dose and time-dependent growth inhibitory effects in both melanoma cells. The IC50 of apatinib at 48 hours in A375 and SK-MEL-28 cells was 62.58 and 59.61μM, respectively, while the IC50 of WZB117 was 116.85 and 113.91μM, respectively. The CI values of the two drugs were 0.538 and 0.544, respectively, indicating a synergistic effect of apatinib combined with WZB117. We also found that glucose consumption and lactate production were suppressed by apatinib plus WZB117 in a dose-dependent manner, paralleled by reducing glycolytic enzyme pyruvate kinase M2 (PKM2). The potential mechanism of the combination was to suppress the phosphorylation of STAT3. Knockdown of STAT3 by siRNA inhibited the expression of PKM2, while the activation of STAT3 by IL-6 increased the expression of PKM2. The effects of IL-6 were attenuated by apatinib combined with WZB117 treatment. Conclusion: WZB117 enhanced the anti-tumor effect of apatinib against melanoma via modulating glycolysis by blocking the STAT3/PKM2 axis, which suggested the combination of apatinib with WZB117 could be a potential therapeutic candidate for melanoma.